Outcomes of endodontic microsurgery using different calcium silicate-based retrograde filling materials: a cohort retrospective cone-beam computed tomographic analysis - Rawan F. Eskandar; Mey A. Al-Habib; Mohammed A. Barayan; Hadeel Y. Edrees (BMC, 2023)
Abstract Purpose To evaluate the outcomes of endodontic microsurgery (EMS) using mineral trioxide aggregate (MTA; Dentsply Sirona, Charlotte, NC, USA), EndoSequence root repair material (RRM putty; Brasseler, Savannah, GA), and injectable Bioceramic (BC) sealer (Brasseler USA) followed by the application of RRM putty (lid technique) as root-end filling materials. Methods One hundred and ten patients who underwent EMS between 2016 and 2020 at King Abdulaziz University Dental Hospital were recruited for clinical and radiographic follow-up after a minimum of 1 year. Radiographic assessment was performed using periapical radiographs (PAs) and cone-beam computed tomography (CBCT). Volumetric analysis of periapical radiolucencies (PARLs) was performed using Amira software. Results Seventy-nine patients (103 teeth: MTA group, n = 28; RRM putty, n = 41; lid technique, n = 34), attended the follow-up visit, with an average follow-up period of 24 months (recall rate = 74.5%). Of the 103 teeth, 40 were anteriors, 24 were premolars, and 39 were molars. All three groups of retrograde filling materials (MTA, RRM putty, and lid technique) showed high success rates on both PA (85.7, 85.4, 94.1%, respectively) and CBCT imaging (67.9, 75.6, 88.2%, respectively), without any significant difference among the success rates of different materials. Overall, a slight agreement was noted between the PA and CBCT outcomes, with a statistically significant difference (P = 0.029). None of the patient-, tooth-, or treatment-related factors significantly influenced the outcomes of EMS. Adequate density of root canal filling material was significantly associated with a high percentage of completely healed cases on CBCT (P = 0.044). PARL volumes were reduced significantly over 1-4 years follow-up after EMS (P < 0.001) Conclusions EMS showed high success rates on both PA and CBCT when MTA, RRM putty or lid technique were used as retrograde filling materials. CBCT imaging is more precise than PA in detecting the healing outcomes of EMS.